The prognostic potential of fragmented CK18 serum levels in HCC patients reflecting disease progression and overall hepatocyte damage - Eguchi, Akiko; Iwasa, Motoh; Tamai, Yasuyuki; Yamada, Minori; Okuno, Koji; Shigefuku, Ryuta; Yoshikawa, Kyoko; Tempaku, Mina; Sakaguchi, Koji; Tanaka, Hideaki; Sugimoto, Kazushi; Kobayashi, Yoshinao; et al. (Frontiers in Oncology, 2022)
Background Fragmented cytokeratin 18 (fCK18) is released from damaged hepatocytes undergoing apoptosis and is recognized as a liver condition biomarker. We have developed a highly sensitive serum fCK18 CLEIA and reported that serum levels of this caspase-derived protein were significantly associated with hepatocyte ballooning, thus assisting in the accurate diagnosis of nonalcoholic steatohepatitis (NASH). We aim to investigate serum fCK18 levels in a variety of chronic liver diseases and to explore its potential as a prognostic marker of survival in hepatocellular carcinoma (HCC) patients. Methods Serum fCK18 levels were measured using a highly sensitive CLEIA in 497 chronic liver disease patients (297 outpatients and 200 hospitalized with HCC). Results In 497 chronic liver disease patients, serum fCK18 levels were significantly correlated with overall liver condition, including ALT, FIB-4 index and albumin-bilirubin (ALBI) score and were significantly increased in patients with HCC. In 200 HCC patients, serum fCK18 levels were significantly correlated with alpha-fetoprotein (AFP) and des-gamma-carboxy prothrombin (DCP), and were significantly associated with HCC stage, whereas FIB-4 index and ALBI score were not changed based on HCC stage. The Survival group had significantly lower levels of serum fCK18, AFP, DCP, FIB-4 index and ALBI score. A ROC analysis yield area under the curve (AUC) value of 0.728 for serum fCK18 is a significantly high value when compared to AUC measurements for other factors. Notably, AUROC values for serum fCK18 levels were constant in the short- and long-term by time-dependent ROC analysis for the prediction of HCC patient survival. HCC patients with serum fCK18 measured at < 1.15 ng/mL, AFP < 7.7 ng/mL, DCP < 133 mAU/mL, ALBI score < -2.97 or FIB-4 index < 6.4 had significantly longer rates of survival when compared to patients with values exceeding these thresholds. Serum fCK18 (HR, 3.5; P < 0.0001), DCP (HR, 3.2; P < 0.0001) and Barcelona Clinic Liver Cancer (BCLC) (HR, 2.4; P = 0.001) values were independent predictors of patient survival. [Conclusion] Serum fCK18 levels reflect overall liver function, the level of liver fibrosis and the progression of HCC, and are a potential predictor of survival in HCC patients.